2006
DOI: 10.1118/1.2208736
|View full text |Cite
|
Sign up to set email alerts
|

Scanning-beam digital x-ray (SBDX) technology for interventional and diagnostic cardiac angiography

Abstract: The scanning-beam digital x-ray (SBDX) system is designed for x-ray dose reduction in cardiac angiographic applications. Scatter reduction, efficient detection of primary x-rays, and an inverse beam geometry are the main components of the entrance dose reduction strategy. This paper reports the construction of an SBDX prototype, image reconstruction techniques, and measurements of spatial resolution and x-ray output. The x-ray source has a focal spot that is electronically scanned across a large-area transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 22 publications
0
101
0
Order By: Relevance
“…19 Briefly, the system uses an electron beam scanned over a large area transmission target with a prepatient multihole collimator. The beams exit the collimator holes and strike the small area, solid state, photon counting detector, creating a series of overlapping narrow field-of-view images from a range of focal spot positions ͑up to 100ϫ 100͒.…”
Section: Iia Sbdxmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Briefly, the system uses an electron beam scanned over a large area transmission target with a prepatient multihole collimator. The beams exit the collimator holes and strike the small area, solid state, photon counting detector, creating a series of overlapping narrow field-of-view images from a range of focal spot positions ͑up to 100ϫ 100͒.…”
Section: Iia Sbdxmentioning
confidence: 99%
“…Scanning-beam digital x-ray ͑SBDX͒ is a low dose inverse geometry fluoroscopy system capable of reconstructing multiple tomosynthetic images in real time, 19 which may overcome some of the shortcomings of conventional QCA. Tomosynthetic reconstruction creates an image corresponding to a physical plane, where structures located in the plane are in focus and structures above and below the plane are blurred.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that radiation dose can be significantly reduced in adult cardiac procedures by using our scanning beam digital x-ray (SBDX) system 4 --a fluoroscopic imaging system that employs an inverse imaging geometry 5,6 ( Figure 1, Movie 1 and Figure 2). Instead of a single focal spot and an extended detector as used in conventional systems, our approach utilizes an extended X-ray source with multiple focal spots focused on a small detector.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatrics procedures are in general much more complex than those performed on adults and thus are on average four to eight times longer 1 . Furthermore, children can undergo up to 10 fluoroscopic procedures by the age of 10, and have been shown to have a three-fold higher risk of developing fatal cancer throughout their life than the general population 2,3 .We have shown that radiation dose can be significantly reduced in adult cardiac procedures by using our scanning beam digital x-ray (SBDX) system 4 --a fluoroscopic imaging system that employs an inverse imaging geometry 5,6 ( Figure 1, Movie 1 and Figure 2). Instead of a single focal spot and an extended detector as used in conventional systems, our approach utilizes an extended X-ray source with multiple focal spots focused on a small detector.…”
mentioning
confidence: 99%
“…21 The electron-beam CT ͑Ref. 22͒ and the scanning beam digital x-ray ͑SBDX͒ 23,24 utilize an electromagnetic field to steer the electron beam to different spots on the x-ray target to produce a scanning x-ray beam without mechanical motion. Such sources are large and, in the case of SBDX, have limited angular range.…”
Section: Introductionmentioning
confidence: 99%